Persepsi Mahasiswa PGSD UNP Mengenai Manfaat Microteaching Terhadap Peningkatan Kompetensi Guru Dalam Aspek Pedagogik Dan Kepribadian - Mai Sri Lena; Hana Shilfia Iraqi; Tuti Erawati; Nulfa Aidina (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This article aims to analyze the perceptions of PGSD UNP students regarding the benefits of microteaching in increasing teacher competence in pedagogic and personality aspects. This type of research is descriptive qualitative. The subjects of this study were active students who took part in Micro Teaching at the S1-PGSD Study Program, Padang State University as well as students who had completed the Micro Teaching course, with a total of approximately 50 students. Data about perceptions were taken using a questionnaire which was distributed through the media google form. The instrument used to obtain research data by filling out a questionnaire. The data analysis technique used in this study is qualitative analysis. The type of scale used to measure data is the Likert scale. The results showed that the benefits of Micro Teaching for PGSD UNP students in increasing competence in the pedagogic and personality aspects have great benefits with the highest percentage of answers to the statements given, namely most students agree with the statements given, with the highest percentage being 70% agree, while for the percentage of perceptions that disagree with all statements is 0%.